The use of works of fiction in the process of teaching writing students of philological specialties - Matvieichenko, V. (Continuing Professional Education: Theory and Practice, 2019)
The aim of the article is to ground theoretically the possibility of using a literary text for teaching writing. In the article the definition of writing is given and the peculiarities of its functioning in writing speech activity are distinguished; psychological and linguistic levels of writing are specified; psychological and linguistic prerequisites for the possibility of using works of fiction to teach students writing are investigated. The process of formation of writing speech activity should be realized with due regard for the content and peculiarities of the functioning of writing; consistently, step by step and only in the course of regular, conscious teaching taking into account both psychological and linguistic levels of writing process organization. Under the conditions of the absence of natural linguistic environment it is possible to create fragments of true communication, to ensure the mastery of lexical and grammatical constructions of natural situations of communication through the use of literary texts in the academic process. A literary text is considered to be the communicative, motive and rich in content basis for the formation and development of writing habits and skills. Such characteristics of a literary text as logicality, consistency and structural clearness favor the formation of coherent and standard writing in which expressed thoughts have systemic and completed character. Sense perception of a foreign literary text is considered to be a stimulus for students’ writing statements.